Qualidade pós-colheita do Maná cubiu frigorificado - Fujita, Erika [UNESP]; Vieites, Rogério Lopes [UNESP] (EIA Energy in Agriculture, 2012)
The aim of this study was to evaluate the effects of temperature on the conservation and fruit quality of Manna cubiu (solanum sessiflorum Dunal) by verifying its physiochemical characteristics. The fruits were harvested in Iguape, SP and taken to the Fruit and Vegetable Laboratory in the Agribusiness Management and Technology Department of the Universidade Estadual Paulista "Julio de Mesquita Filho", campus de Botucatu, SP where experiments and analysis were conducted. The experiment was conducted and storage temperatures of (ambient 24 ± 3°C, 6°C, 8°C and 10°C). The fruits were evaluated for soluble solids, acidity, maturation index "Ratio" and pH. The experiment design was factorial in a 4 x 6 ratio (4 days of temperature x 6 days of storage). The treatment means and interactions were comported using the Tukey test at 5% probability. The fruits at 10°C presented the best results while maintaining their quality during the post-harvest storage period.

O presente trabalho teve o objetivo de avaliar os efeitos de temperaturas na qualidade e conservação do fruto de Maná cubiu (Solanum sessiflorum Dunal) verificando suas características físicoquímicas. Os frutos foram colhidos no município de Iguape-SP e levados para o Laboratório de Frutas e Hortaliças do Departamento de Gestão e Tecnologia Agroindustrial da Universidade Estadual Paulista "Julio de Mesquita Filho", Campus de Botucatu – SP, onde foi instalado o experimento e realizadas as análises. O trabalho foi conduzido em temperaturas de armazenamento (ambiente 24 ± 3°C, 6°C, 8°C e 10°C). No experimento os frutos foram avaliados quanto aos sólidos solúveis, acidez titulável, índice de maturação "Ratio", pH. O delineamento experimental foi em esquema fatorial 4 x 6 (4 temperaturas x 6 dias de armazenamento). As médias dos tratamentos e as interações foram comparadas utilizando-se o Teste de Tukey a 5% de probabilidade. Os frutos a 10°C apresentaram os melhores resultados mantendo a qualidade pós-colheita durante o período de armazenamento.
Post-harvest quality of cooled Manna cubiu
Keywords: Solanum sessiflorum Dunal; Refrigeration; Solanum sessiflorum Dunal; Refrigeração